Investigator beliefs of homicide crime scene characteristics - Reynolds, Joshua J. (Applied psychology in criminal justice, 2019)
Homicide investigators rely on a plethora of sources to solve a case, including their own beliefs and intuitions. We discuss a variety of these beliefs and explore their veracity using a novel approach, coding cases from the documentary television show, Forensic Files. Our results indicate that most of these beliefs are unsupported. However, some beliefs may be predictive. Specifically, a body that was wrapped or placed in a container was indicative that the body had been transported. In addition, finding the victim nude was predictive of rape. We discuss the problems of following inaccurate beliefs, and the potential use of the accurate beliefs we identified.